Manajemen Wakaf dan Peranannya Pada Perguruan Tinggi - Gustina - Gustina; Hidayatul Ihsan (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2019)
Communal ownership has proved successful in supporting and improving the welfare of society, including education. Many sectors in society that can already be supported by waqf, such as facilities of worship, hospitals, education, economic facilities and others. Study waqf in higher education was still relatively rare for Indonesia. In the world, however, there are many universities that carry out of the principle of communal ownership, such as Al-Azhar University at Cairo University of Cordoba Spain and so on. This artilce aimed to explore the application of communal ownership for higher education from management and economics. The method used literature review of books, manuscripts and publications of scientific journals. The results of the study indicated that the continuity and sustainability of the use of communal ownership in society was determined by the management of communal ownership by the manager (Nazhir) and the foundation of the trustee holder of the communal ownership. Key words: Management Communal Ownership, Communal Ownership in Education